THE ROLE OF FINANCIAL INNOVATION IN PROMOTING GROWTH AND INNOVATION OF FINANCIAL INSTITUTIONS: A CASE STUDY OF RAFIDAIN BANK - Lina Tariq Ali (Scholars Digest Publishing, 2024)
This study aims to evaluate the impact of financial innovation on economic growth and financial services in Rafidain Bank and to analyze the factors that affect the success of financial innovation and its associated challenges. This study was limited to the sample of Rafidain Bank (employees, department heads, and general managers), which was a stratified random sample of 100 employees, using a descriptive survey method as an appropriate research method as the questionnaire was conducted using statistical procedures (SPSS Ver. 27). The results showed that: The application of financial innovations in Rafidain Bank has improved financial services, increased profitability, and competitiveness. Therefore, the institution has promoted growth and innovation; based on these findings, the researchers recommend that: There is a need to develop new policies and procedures to encourage and support financial innovation and mitigate the barriers and challenges associated with it, which represents a continuous challenge to promote innovation in the financial services industry and achieve strong and sustainable development.
Keywords: innovation, technology, policies and legislation, partnership and cooperation, growth.